Kontekstualisasi Ayat-Ayat tentang Kepemimpinan dalam Al-Qur’an (Studi Fenomena Politik Identitas Indonesia) - Rani Martia Sari; Muhammad Noupal; Deddy Ilyas (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2023)
This research is entitled "Contextualization Of Verses About Leadership in The Qur'an" (Study of Political Phenomena of Indonesian Identity)". The background of this research is of the term leadership in the contemporary era. There has been a lot of disharmony between religious communities that has deprived other people of their basic rights, resulting in discrimination and oppression due to leadership issues. Even though the essence of the truth of leadership in a religion is the formation of a prosperous, just and prosperous society (Baldatun Toyyibatun Wa Rabbun Ghafur) Islam does not provide a formal leadership and state administration system for its people, however, the Koran as the main source of teachings provides principles universal about leadership in the holy book, as for the form of words or meanings that have the criteria and characteristics of a leader described in several letters and verses in the Koran. Against this background, the problem is formulated, how is the contextualization of the verses of the Koran about leadership towards the phenomenon of identity politics in Indonesia? and What aspects are contained in the contextualization of the verses of the Koran about leadership towards the phenomenon of identity politics in Indonesia? The type of research that will be used is library-based research (library research). The research is carried out by taking data sources from library, then selecting these data, and analyzing these data. This research is basically main source, namely the verses that discuss leadership and how the phenomenon of Indonesian Identity Politics.